2014
DOI: 10.1177/0272431614549627
|View full text |Cite
|
Sign up to set email alerts
|

Family Socioeconomic Status and Academic Achievement Among Korean Adolescents

Abstract: This study examined pathways through which family socioeconomic status may influence adolescents’ academic achievement. We focused on parental monitoring and adolescents’ after-school time-use patterns as linking mechanisms. Participants were 441 twelve- to fourteen-year-old Korean adolescents who participated in the Korea Welfare Panel Study. Higher family economic pressure was linked with lower parental monitoring through elevated levels of parental depression. Parental monitoring was associated with more ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 54 publications
4
47
0
1
Order By: Relevance
“…Our findings are in accordance with a significant body of literature that reported these sorts of activities to be predictive of antisocial and norm-breaking behaviours (Augustyn and McGloin 2013; Haynie and Osgood 2005; Hoeben and Weerman 2016) or linked to worse school performance (Bae and Wickrama 2015; Nelson and Gastic 2009) and increased rates of substance use (Lee and Vandell 2015; Spilkova 2015). UA appear to attract adolescents who generally incline towards health-risk and delinquent behaviours (Mahoney et al 2004; Persson et al 2007), and exposure to such peers is one of the frequently discussed reasons for the negative outcomes of UA (Haynie and Osgood 2005; Hoeben and Weerman 2016; Svensson and Oberwittler 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in accordance with a significant body of literature that reported these sorts of activities to be predictive of antisocial and norm-breaking behaviours (Augustyn and McGloin 2013; Haynie and Osgood 2005; Hoeben and Weerman 2016) or linked to worse school performance (Bae and Wickrama 2015; Nelson and Gastic 2009) and increased rates of substance use (Lee and Vandell 2015; Spilkova 2015). UA appear to attract adolescents who generally incline towards health-risk and delinquent behaviours (Mahoney et al 2004; Persson et al 2007), and exposure to such peers is one of the frequently discussed reasons for the negative outcomes of UA (Haynie and Osgood 2005; Hoeben and Weerman 2016; Svensson and Oberwittler 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Nearly all Korean high school students also go to private after-school institutions or stay at school for evening individual study that may continue until 22:00. Under strong sociocultural and psychological influences emphasizing the importance of college entrance examinations, Korean adolescents further curtail their sleeping time (Bae & Wickrama, 2015). In addition, the quality and amount of parental involvement and investment in children’s academic performance seem to cause excessive stress for adolescents (Kim & Lee, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies generally showed a positive relationship between ESCS and problem-solving or mathematics performance (Akyüz & Pala, 2010;Alacacı & Erbaş, 2010;Bae & Wickrama, 2015;Perkins & Shiel, 2014). In PISA 2012 mathematics assessment, socio-economically advantaged students scored on average 78 points higher than disadvantaged students (OECD, 2013d).…”
Section: Walberg's Environmental Variablementioning
confidence: 89%
“…Economic, social and cultural status (ESCS) is an occupational, educational, wealth, and cultural indicator of a family. Many studies showed that there was a positive relationship between ESCS and problem-solving or mathematics performance (Akyüz & Pala, 2010;Alacacı & Erbaş, 2010;Bae & Wickrama, 2015;Perkins & Shiel, 2014). Experience with pure and applied mathematics tasks at school are opportunityto-learn indicators that showed a significant relationship with performance in PISA (Schmidt, Zoido, & Cogan, 2014).…”
Section: Factors Predicting the Problem-solving Performance Differencesmentioning
confidence: 99%